(untitled) (Mustansiria Dental Journal, 2023)
Background: One of the serious challenges in dental treatment is socket healing after tooth extraction. Various researchers have attempted to develop efficient therapies for healing and regenerating damaged tissues after extraction. Many tissue engineering technologies have been used now a day to enhance tissue healing. Aim: The present study was planned to evaluate the efficacy of epidermal growth factor with synthetic hydroxyapatite powder in socket healing. Methods: six-Thirty male rats were included in this study and their lower incisors teeth were subjected to extraction. Animals were divided into the following three groups according to socket treatment. (A) control, socket hole left to heal without any application, (B)application of hydroxyapatite powder (HAP) in the socket, (C) application of epidermal growth factor (EGF) with hydroxyapatite powder in the socket. Histological evaluation for bone formation, bone cell and inflammatory cell count with histomorphometry of bone trabeculae percentage had been done to all study groups and for three periods (5,14 &28 days). Results: Epidermal growth factor with hydroxyapatite group showed early bone formation, more bone cell count, and less inflammatory cell infiltration in comparison to the HAP group and control at periods (5,14&28 days) and with a statistically significant difference (p<0.05). Bone trabeculae percentage was recorded to be high in the HAP&EGF group that filled the socket hole at (14 ,28 days) intervals in comparison to hydroxyapatite and control group. Complete re-epithelialization was observed only in the EGF&HAP group. Conclusions: Both the HAP&EGF group and the hydroxyapatite group show bone formation and good socket healing, but the EGF&HAP group showed to be faster in filling of boney socket hole with complete epithelization than hydroxyapatite group, therefor using EGF with HAP is more efficient and suggested the material of choice used for socket healing.